ASSESSMENT OF COGNITIVE CHANGES IN EARLY SCHOOL-AGE CHILDREN WITH SEIZURE SYNDROME (International journal of artificial intelligence, 2026)
Seizure syndrome in childhood is frequently associated with cognitive and behavioral disturbances that may interfere with academic performance and psychosocial development. Early school age represents a critical period for the maturation of higher cognitive functions, including attention, memory, and executive abilities. This article analyzes cognitive changes observed in early school-age children diagnosed with seizure syndrome. Particular emphasis is placed on the assessment of attention, memory, learning abilities, and executive functioning, as well as the influence of seizure characteristics and antiepileptic treatment. Early identification of cognitive impairments is essential for timely intervention and optimization of educational and rehabilitation strategies.